Detection of Sea, Seb, Sec, Seq genes in staphylococcus aureus isolated from nasal carriers in Tehran province, Iran; by multiplex PCR - Saadati, Mojtaba; Barati, Babak; Doroudian, Mohammad; Shirzad, Hadi; Hashemi, Mehrdad; Hosseini, Saed Mostafa; Salehi Chaleshtari, Ahmad Reza; Bahmani, Mirza-Khalil; Hosseinzadeh, Saeid; Imani, Saber (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Staphylococcus(S.) aureus produces different extra-cellular protein toxins and virulence factors. One of the most important extra-cellular proteins is an enterotoxin which causes staphylococcal food poisoning (SFP) due to their enterotoxins. Different methods have been used to detect this toxin, each of which has advantages and disadvantages. DNA amplification methods, however, can show the presence of enterotoxigenic strains of S. aureus before the expression of enterotoxins on the basis of specific gene sequences. In this study, 150 S. aureus strains isolated from nasal carriers were confirmed by biochemical testing. PCR was used to amplify the staphylococcal enterotoxin A, B, C and Q genes, as well as the staphylococcal nuclease gene. Among the 150 healthy human isolates from the nasal carrier, 95 were confirmed as S. aureus. Only 58.9% of the isolates were diagnosed as sea, b, c, q positive. There were 24 (25.3%) isolates associated with the sea gene, 15.8% isolates associated with the seb gene, 9.5% of the isolates were associated with the sec gene, and 8.4% of the isolates associated with the seq gene. Of these isolates, 41% might be possessing additional se genes but they were not see (178 bp) and sed (319 bp) genes. The nuc gene, which encodes thermo nuclease, was used as a target DNA to identify S. aureus. Additionally, one of these enterotoxigenic isolates carried more than one toxin gene.